Program “Pilar” untuk Meningkatkan Pengetahuan dan Keterampilan Ibu Menyampaikan Prevensi Kekerasan Seksual Anak - Nurhuzaifah Amini; Ira Paramastri (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
The number of negative impacts caused by CSA makes it still need serious treatment. Mother as the closest environment of early childhood should be able to be a preventive agent of CSA. In fact, there was still many mothers who do not have knowledge dan skill regarding CSA prevention on children. Therefore, a program was needed to improve the knowledge and skills of parents through the “PILAR” program (Skilled-Taught Self Protection Skill). This study aimed to validate the “PILAR”program through content validation with professional judgement and empirical validation with training using the one pretest and posttest group design. The result showed that knowledge about CSA prevention improves significantly after being given training with Z = -2.952, p = 0.003 (p < 0.01) and CSA prevention skills improve significantly with Z = -2.952, p = 0.003 (p < 0.01). It meant that the program of “PILAR” was able to improve the knowledge and skills of mothers in performing prevention of CSA.